An array of fabry-perot optical-channels for biological fluids analysis - Minas, Graça (2004)
This paper describes a biosystem (biological system) used to measure the concentration of biochemical substances in urine, serum, plasma or cerebrospinal fluid. Rather than just one channel, it comprises 16 optical-channels that enable the measurement of the concentration of 16 different biochemical substances. An array of 16 optical filters based on Fabry-Perot thin-films optical resonators has been designed. Each optical-channel is sensitive in a single wavelength with a full-width-half-maximum (FWHM) of 7 nm. The filter fabrication requires only four masks, used with different etch time. A commercially available band-pass optical filter with a band-pass wavelength in 450–650 nm is used. The biosystem requires only a white light source for illumination due the use of selective optical filters.